Prehospital interventions in severely injured pediatric patients: Rethinking the ABCs - Sokol, Kyle K; Black, George E; Azarow, Kenneth S; Long, William; Martin, Matthew J; Eckert, Matthew J (The journal of trauma and acute care surgery, 2015)
The current conflict in Afghanistan has resulted in a high volume of significantly injured pediatric patients. The austere environment has demanded emphasis on prehospital interventions (PHIs) to sustain casualties during transport. The Department of Defense Trauma Registry was queried for all pediatric patients (≤18 years) treated at Camp Bastion from 2004 to 2012. PHIs were grouped by Advanced Trauma Life Support categories into (1) airway (A)--intubation or surgical airway; 2) breathing (B)--chest tube or needle thoracostomy; and 3) circulation (C)--tourniquet or hemostatic dressing. Outcomes were assessed based on injury severity, hemodynamics, blood products and fluids, as well as mortality rates. There were 766 injured children identified with 20% requiring one or more PHIs, most commonly circulation (C, 51%) followed by airway (A, 40%) and breathing (B, 8.7%). The majority of C interventions were tourniquets (85%) and hemostatic dressings (15%). Only 38% of patients with extremity vascular injury or amputation received a C intervention, with a significant reduction in blood products and intravenous fluids associated with receiving a C PHI (both p < 0.05). A interventions consisted of endotracheal intubation for depressed mental status (Glasgow Coma Scale [GCS] score < 8). Among patients with traumatic brain injury, A interventions were associated with higher unadjusted mortality (56% vs. 20%, p < 0.01) and remained independently associated with increased mortality after multivariate adjustment (odds ratio, 5.9; p = 0.001). B interventions were uncommon and performed in only 2% of patients with no recorded adverse outcomes. There is a high incidence of PHIs among pediatric patients with severe wartime injuries. The most common and effective were C PHI for hemorrhage control, which should remain a primary focus of equipment and training. A interventions were most commonly performed in the setting of severe traumatic brain injury but were associated with worse outcomes. B interventions seem safe and effective and may be underused. Care management/therapeutic study, level IV.